Dakwah dan Konseling dalam Menghadapi Isu Kesehatan Mental di Indonesia - Maharani, Reizki; Yazid, Yasril; Rafdeadi, Rafdeadi; Azwar, Azwar (Idarotuna, 2024)
Mental health is an issue that is receiving more attention in Indonesia, especially amidst rapid social and cultural changes. This research explores the role of religious preaching (dakwah) and counseling in addressing societal mental health problems. The method used in this research is literature study. The authors gathers and analyzes various relevant sources, including journal articles, books, and reports from related institutions. The main findings of this research show that dakwah can be an effective tool in increasing awareness and understanding of mental health among the public while counseling based on religious values can provide the emotional and spiritual support needed by individuals experiencing mental health problems. The implications of this research emphasize the importance of collaboration between mental health practitioners and religious leaders to create a holistic approach to addressing mental health issues in Indonesia.